The relationship between sensorimotor perceptions and the perception of the ball's landing point and the match result for volleyball players (The International Journal for Scientific Research, 2026)
This research aims to study the relationship between volleyball players' sensorimotor abilities and their ability to perceive the ball's landing point, as well as the impact of this ability on the outcome of the match. The research hypothesizes that players with better sensorimotor perceptions will be more accurate in predicting the ball's landing location, giving them a strategic advantage that contributes to achieving better results in matches. The research addressed the identification and evaluation of volleyball players' sensorimotor perceptions. The ability to perceive the ball's landing point was measured, and the relationship between sensorimotor perceptions and the perception of the landing point was analyzed. The research was applied to a sample of (86) volleyball players using a descriptive approach. Tests were used for visual perception, sensorimotor perception, temporal and spatial perception, and complex sensorimotor perception. The level of experience (high -low), perception of the ball's landing point, and prediction of the match outcome were considered average. The research results showed that visual perception ranked first at a high level, followed by temporal and spatial perception and sensorimotor perception at an average level, and finally, complex sensorimotor perception at an average level. There was a strong positive correlation between sensorimotor perceptions and the perception of the ball's landing point. The participants' ability to predict the ball's trajectory and accurately determine its landing point improved. The strongest correlation was between complex sensorimotor perception and the perception of the ball's landing point, indicating the importance of integrating various types of sensorimotor perceptions in improving prediction accuracy. The study recommended that coaches focus on developing players' sensorimotor perceptions by designing specialized training programs that target improving various types of sensorimotor perceptions (visual perception, sensorimotor perception, spatial-temporal perception, and complex sensorimotor perception).
Keywords: Sensorimotor; Visual Perception; Sensorimotor Perception; Ball Landing Point; Level of Experience